PERMINTAAN PENJELASAN ATAS DATA DAN/ATAU KETERANGAN DALAM PERSPEKTIF KEPASTIAN HUKUM DAN PRINSIP PELINDUNGAN DATA PRIBADI : Requests For Explanation Of Data And/Or Information From The Perspective Of Legal Certainty And Principles Of Personal Data Protection - Albertus (Fakultas Hukum, Universitas Trisakti, 2025)
This study aims to examine the legality of the Request for Clarification of Data and/or Information (P2DK) activity within Indonesia's tax administration system, particularly from the perspective of legal certainty and personal data protection principles. In practice, the Request for Clarification of Data and/or Information has become a routine compliance monitoring tool by the Directorate General of Taxes (DGT). However, it lacks an explicit legal basis in statutory regulations and is only governed through Director General Circular Letter SE-05/PJ/2022. This raises serious legal concerns, especially since data requests under the Request for Clarification of Data and/or Information have the potential to infringe upon taxpayers’ right to privacy. Using a normative legal research type with a statute and conceptual approach, this study finds that the absence of formal legal foundation for the Request for Clarification of Data and/or Information contradicts the theory of legal certainty as proposed by Gustav Radbruch and the data protection principles stipulated in Law No. 27 of 2022. Therefore, the study recommends that the Request for Clarification of Data and/or Information be repositioned within the positive legal framework through regulation at the statutory level to ensure the protection of taxpayers’ constitutional rights and provide legal legitimacy for Directorate General of Taxes in carrying out its supervisory functions